Association study and meta analysis of nrg 1 genes (rs2954041) with schizophrenia - Ong, Huee Pin (2023)
Schizophrenia is the most persistent mental illness. The etiology of schizophrenia is still unknown however, various studies have shown that there are genetic factors in the pathogenesis of schizophrenia. The neuregulin-1 (NRG1) gene is one of the most potent schizophrenia risk genes. Neurotransmitter activity is correlated with each of the four NRG1 genes. The objective of this study is to examine the association between rs2954041 of NRG1 with schizophrenia in Malaysian populations (Malay, Chinese and India). Meanwhile, gender for the pathogenesis of schizophrenia was also observed in this review. Meta-analysis was used to combine the findings for this study with several studies addressing a range of related research hypotheses. There was a total of 44 samples for both healthy controls and patients in this study. DNA sequencing was used to confirm the genotyping of NRG1 SNP rs2954041 using the polymerase chain reaction-restriction fragment length polymorphism technique (PCR-RFLP). Statistical analysis of the observatory data shows that there was an association (p < 0.005) of rs 2954041 of NRG 1 with schizophrenia by ethnic. Meanwhile, there was no association (p > 0.005) of rs2954041 of NRG 1 with schizophrenia by gender and the total pooled samples. The significant association of rs2954041 of NRG1 with schizophrenia by ethnic might be a false association which was affected by the small sample sizes. The homozygous genotype, G/G (guanine/guanine) appeared the most in this study, the risk allele is the thymine(T) which the low frequency of ‘T’ resulted in an insignificant result. The results suggest that the rs2954041 of NRG1 do not play an important role in development of schizophrenia, however, further study is necessary to further confirm the result.